Tumor Stroma as a Target in Cancer - Ahmed, F.; Steele, J. C.; Herbert, J. M.J.; Steven, N. M.; Bicknell, R. (Current Cancer Drug Targets, 2008)
Solid tumors are composed of the malignant cell itself (most commonly a carcinoma) and supporting cells that comprise the stroma. Significant stromal components include the extracellular matrix, supporting fibroblasts, vessels comprised of endothelium, pericytes and in some cases vascular smooth muscle, lymphatics and usually a major leukocyte infiltration. Indeed, macrophages may constitute up to 50% of the viable cells within the tumor. For many years, researchers have concentrated almost exclusively on the malignant carcinoma and looked for ways to either selectively kill or restrict its growth. In recent years the frustrating lack of advances in cytotoxic cancer therapy provoked a search for more novel strategies and foremost amongst these were anti-angiogenesis and vascular targeting. The purpose of this article is to illustrate how the stroma is now being pursued as an anti-cancer target. The article will briefly touch on antiangiogenics that are now entering the clinic but concentrate on recent studies looking at vascular disrupting agents, stromal tumor fibroblasts and macrophages. Target identification is illustrated by the search for tumor endothelial markers. Finally, we draw attention to efforts to develop a cancer vaccine. The genetic instability and variation found in carcinoma cells made vaccination in the past a near impossibility. In contrast, genetically stable tumor endothelium with its unique accessibility to blood borne agents, together with recent advances in immunotherapy means that the possibility of a cancer vaccine now takes on a reality not previously recognised.
Keywords: tumor endothelial marker